USE OF PREPARATORY GAMES IN A FOREIGN LANGUAGE LESSON - Halikova Shakhlo Uktamovna (Galaxy International Interdisciplinary Research Journal, 2021)
The article analyzes the use of preparatory games in a foreign language lesson. Preparatory games are games aimed at developing language skills and abilities. They are grammatical, lexical, phonetic, spelling. Each group of games is considered in detail.